Smart Tech Study Table / Nur Amira Aminuddin - Aminuddin, Nur Amira (2020)
The problem statement is important to be listed and analysed. This is because this process let us aware and identifies the weakness of the current product. Therefore, the new product development can be planned and formed by thinking the best method to improve the current product becoming the preferable and greater product. The current product has the same functions with the other similar products from different production or company. The demand of the product can be assume as high because this product likely to be convenience and suitable for everyone despite of their ages. However, by having the similar product with the others can cause the demand for the certain company is lower since there are many competitors. Besides, the current products usually have the limited space. This problem is common since the current study table is created to be small to able it can be handled easily without much effort. The consumer uses the study table to do their tasks and work where the might be place their stuffs such as laptop, books, stationary and paper on it. Therefore, by having limited space causes the consumer unable to place their stuffs at the floor instead of on the table. Next, the current product is lacking at the implementation of the technology. Nowadays, the technology is necessary to help the people by making the tasks more convenience and easier. Without the technology, they will require to do the task manually which it can take some times and causes any problem or mistake. Thus, the error that has been made can cause the consumer to be in trouble especially if the error is massive. For instance, the consumer needs to make a calculation and there is no calculator is available at that moment in which leads him to do the calculation manually by using paper and pen.